BIOSURFACTANT PRODUCTION BY HALOPHILIC BACTERIA - JAYSREE, R.C.; RAJAM, C.; RAJENDRAN, N. (International Journal of Pharma and Bio Sciences, 2013)
Biosurfactants that are synthesized by microorganisms are capable of reducing surface and interfacial tension with low toxicity and high specificity. In this study, two bacterial strains JS05 and JS06 were isolated from the soil near to a fishery storage plant containing high salt content. Molecular analysis of these strains revealed that they were Brevibacterium lutescens (JSO5) and Bacillus sp. (JSO6). Both of them were screened for the production of biosurfactant by oil spreading test, emulsification activity and blood hemolytic test. Both the strains showed the capability to produce biosurfactant, but Brevibacterium lutescens (JS05) showed better activity when compared to Bacillus sp. (JS06) giving a oil displacement of about 4cm and emulsification index of 68%. The results of this study suggested that these two bacterial strains could be considered as potential candidates for biosurfactant production, but needs to be studied further for field application.